2020
DOI: 10.1371/journal.pone.0231144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phenotyping of shell suture strength in walnut (Juglans regia L.) enhances precision for detection of QTL and genome-wide association mapping

Abstract: Walnut shell suture strength directly impacts the ability to maintain shell integrity during harvest and processing, susceptibility to insect damage and other contamination, and the proportion of kernel halves recovered during cracking. Suture strength is therefore an important breeding objective. Here, two methods of phenotyping this trait were investigated: 1) traditional, qualitative and rather subjective scoring on an interval scale by human observers, and; 2) quantitative and continuous measurements captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…By comparison with other walnut panels used for GWAS, we observed a larger degree of fruit phenotypic variability. For instance, in the panel used in Iran, the range for nut weight was between 7.71 and 20.11 g (Arab et al, 2019), whereas in our panel, combining all the years studied, the range was between 5.22 and 22.51 g. Similarly, in the work on suture strength reported by the University of California, Davis, the use of a texture analyzer to phenotype suture strength showed a variation between 6.94 to 63.14 kg-force (i.e., between 68.06 to 619.19 N) among the 556 accessions studied (mainly from 39 biparental progenies) corresponding to a variation of 551.13 N (Sideli et al, 2020). In our walnut germplasm, with only 170 accessions and combining all the years, the variation extends from 74.40 to 776.97 N. With the high phenotypic variability and the diversity of the INRAE walnut panel used for GWAS analysis, knowing that most of these traits are highly quantitative, we may expect to find major loci involved in their variation.…”
Section: The Inrae Walnut Germplasm Collection Has a High Degree Of Fsupporting
confidence: 56%
See 2 more Smart Citations
“…By comparison with other walnut panels used for GWAS, we observed a larger degree of fruit phenotypic variability. For instance, in the panel used in Iran, the range for nut weight was between 7.71 and 20.11 g (Arab et al, 2019), whereas in our panel, combining all the years studied, the range was between 5.22 and 22.51 g. Similarly, in the work on suture strength reported by the University of California, Davis, the use of a texture analyzer to phenotype suture strength showed a variation between 6.94 to 63.14 kg-force (i.e., between 68.06 to 619.19 N) among the 556 accessions studied (mainly from 39 biparental progenies) corresponding to a variation of 551.13 N (Sideli et al, 2020). In our walnut germplasm, with only 170 accessions and combining all the years, the variation extends from 74.40 to 776.97 N. With the high phenotypic variability and the diversity of the INRAE walnut panel used for GWAS analysis, knowing that most of these traits are highly quantitative, we may expect to find major loci involved in their variation.…”
Section: The Inrae Walnut Germplasm Collection Has a High Degree Of Fsupporting
confidence: 56%
“…For cracking related traits, using different phenotyping methods and FarmCPU model, the MTA AX-170748528 (Chr5, 13,023,760 bp) was found to be associated with the suture strength ( Sideli et al, 2020 ). This MTA was only 762 bp apart from the SNP just below the significant threshold obtained for the suture strength initial rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the QTL mapping analysis, the ‘Idaho’ genetic map which was constructed in ( Sideli et al 2020 ) was found to have nearly a twofold increase range in map size of ‘Chandler’ genetic map. Shorter genetic maps of female parent in walnut and other species has also been observed ( Luo et al 2015 ; Kefayati et al 2019 ; Marrano et al 2019 ) thereby suggesting a lower recombination rate in the female parent of walnut.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative-trait loci mapping was performed using the genetic maps (File S5) of the bi-parental population ‘Chandler’ × ‘Idaho’ described in ( Sideli et al 2020 ). In particular, the ‘Chandler’ genetic map spanned 998.31 cM with 1,165 markers in total, while the ‘Idaho’ map contained 1,753 markers for a total length of 1,693.88 cM.…”
Section: Methodsmentioning
confidence: 99%